Development of Pedicure Learning Videos for Vocational Students Using ADDIE Model - Kartikasari, Lintang; Nurhadi, Didik; Nurjannah, Nunung (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Videos can serve as an effective teaching tool, motivator, and focus for students during learning tasks. The goal of this project is to create ADDIE pedicure learning films that will aid in the comprehension of pedicure material for VHS skin and hair beauty majors. Research and development using the Analysis, Design, Development, Implementation, and Evaluation development paradigm is what this kind of study is called. thirty students from class X Phase E Skin and Hair Beauty served as the research subjects for the study, which was carried out at VHS State 2 Boyolangu, Tulungagung, with a focus on skin and hair beauty. The findings demonstrated that: (1) analysis by observation and interviewing, (2) design goods made with software, (3) In order to fill out validation questionnaires, researchers conducted feasibility tests with a number of experts, including language, IT media, material experts, and students. Researchers that specialize in implementation conducted trials in step four. In step five, they examined the recommendations and comments provided by validators and analyzed data based on the efficacy test findings, namely the pretest and posttest. The study's conclusion is that instructors can employ learning videos that incorporate the ADDIE growth stages to give their students nail care resources in a practical and efficient manner.